Man-Wildlife Conflict due to Agriculture Practice in The Fringe Areas of Little Rann of Kachchh (LRK), Gujarat, India - Joshi, Darpak; Tatu, Ketan; Joshi, Jigar D.; Kamboj, R. D. (Indian Forester, 2019)
Rural or tribal communities and wildlife in different parts of the country have a long history of co-existence with variable types and intensity of Man-wildlife interaction. In the past, intensity of Man-wildlife competitive interaction for common resources might have been less due to low human population. In turn, ample space to inhabit and sufficient life supporting resources were available for man and wildlife. Thus, in the past there might be a limited confrontation between man and wild animals for daily life requisites like land, food and water. However, in the present time-frame, due to ever-increasing human population land utilization and natural resource exploitation by man has increased to substantial levels. In turn, in the present era, chances of confrontation between rural/tribal communities and wildlife sharing the same localities for available natural resources have increased in various parts of the country including those in Gujarat state. Existence of high population of human beings and their livestock and good population of a variety of wild ungulates and predators in a landscape such as the Little Rann of Kachchh (LRK), often lead to Man-wildlife friction which further give rise to undesirable effects on social, economic and cultural life of man and conservation of wildlife. An attempt is made through the present study to assess this scenario in the context of man-wildlife interaction due to crops, which constitute a natural resource shared by man and Wild Ass in the fringe areas of LRK.